Tinjauan Yuridis terhadap Implementasi Metode Kelulusan Skripsi dan Non-Skripsi di Perguruan Tinggi - Surya, Adi; Chondro Kismo Pratomo (JUSTITIABLE - Jurnal Hukum, 2024)
This study aims to examine the implementation of graduation methods in Indonesian universities, both through thesis and non-thesis routes, considering the legal framework, challenges faced, and its juridical implications. The research method used is normative legal research with Statute, Conceptual, and Historical approaches. The results indicate that legal regulations provide autonomy to universities to determine graduation methods, but various interpretations and applications result in legal uncertainty and a gap between theory and practice. Challenges faced include limitations in human resources and administrative complexity. To address this, universities need to improve guidance quality, optimize resources, and simplify administrative procedures. In conclusion, effective implementation of graduation methods will enhance the quality of higher education and institutional reputation, in line with established national and international standards. Keywords: Graduation Methods, Universities, Thesis, Non-thesis.